Youth cultures and career pathways – a well-being perspective on sticker artists' cultural and professional engagements in St. Petersburg. Issue 1 (April 2023) - Vasileva, Nadezhda; Honkatukia, Päivi
Based on multiple interviews and observations in St Petersburg, Russia 2016–2021, this article suggests using the theory of sustainable well-being to describe the nexus of sticker art as youth cultural engagement and working life. We assume that this theoretical toolkit is applicable to the analysis of the dynamic relationships between various spheres of young people's lives and tensions caused by diverse societal structures. Our scrutiny reveals that engagement with sticker art may be involved in the quest for well-being and filling voids that working life has failed to fill at the material and ontological levels. The article approaches the post-Fordist work ethic critically, likewise the excessive encroachment of work on young people's lives. The paper challenges the assumptions of the primacy of work in meeting young people's basic needs and analyses how young people acquire personal value through their engagements in DIY youth culture.